Inhibition by Glaucocalyxin A of Aggregation of Rabbit Platelets Induced by ADP, Arachidonic Acid and Platelet-Activating Factor, and Inhibition of [3H]-PAF Binding - Bin, Zhang; Kun, Long (Thrombosis and Haemostasis, 1992)
Glaucocalyxin A is a new diterpenoid isolated from the ethereal extract of the leaves of Rabdosia japonica (Burm f) Hara var glaucocalyx (Maxim) Hara (Labiatae) collected in the northeastern China. When it was incubated with washed rabbit platelets, glaucocalyxin A inhibited ADP- or arachidonic acid-induced platelet aggregation with IC50 values of 4.4 μmol/1, 14.1 μmol/1 respectively. Glaucocalyxin A also inhibited PAF-induced aggregation of rabbit platelets which were refractory to ADP and arachidonic acid with an IC50 value of 13.7 μmol/1. Analysis of [3H]-PAF binding showed that glaucocalyxin A prevented [3H]-PAF binding to intact washed rabbit platelets with an IC50 value of 8.16 μmol/1, which was consistent with its inhibition of PAF-induced platelet aggregation.